PENGARUH KENAIKAN TARIF HAJI TERHADAP MINAT PENDAFTAR HAJI DI KOTA METRO - Faris, Qashmal Hawali; Dewi Chan, Sukma Sari (Multazam : Jurnal Manajemen Haji dan Umrah, 2024)
From an economic perspective, the Hajj pilgrimage is related to the financial capacity of the people who are able to carry out the Hajj pilgrimage. To be able to carry out the Hajj, prospective pilgrims will be charged a Hajj tariff or what is usually called BIPIH (Hajj Travel Fee). The government and DPR have agreed on an average BPIH for 1444H/2023M for regular Hajj pilgrims of IDR 90,050,637. This figure consists of two components, namely BIPIH which is borne by the congregation on average IDR 49,812,700 and the use of the benefit value per congregation is IDR 40,237,937. Hajj rates experience quite significant increases every year, this year due to the dollar exchange rate and the riyal exchange rate. Based on this statement, this research aims to determine the interest of Hajj registrants in metro cities. The method used in this research is quantitative, the population in this research is a metro city with a sample of Hajj registrants in 2022. The sampling technique used is purposive sampling. In a simultaneous test, it was discovered that the variable increasing the Hajj tariff had a significant effect on the interest of Hajj registrants.